How national and international financial development affect industrial R&D - Keith E. Maskus; Rebecca Neumann; Tobias Seidel (Center for Economic Studies and ifo Institute (CESifo), 2011)
We examine the impacts of both domestic and international financial market development on R&D intensities in 22 manufacturing industries in 18 OECD countries for the period 1990- 2003. We take account of such industry characteristics as the need for external financing and the amount of tangible assets. Multiple forms of domestic financial development are important determinants of R&D intensity but only foreign direct investment is significant among alternative measures of international financial development. We find the strongest effects for private bond-market capitalization, while FDI, private credit by banks, and stockmarket capitalization have similar effects in terms of magnitude.
Keywords: F36; G10; G15; G32; O30; 330; R&D; financial systems; financial development; international financial integration; Industrielle Forschung; Forschungsfinanzierung; Finanzsektor; Finanzmarkt; Internationaler Finanzmarkt; Direktinvestition; Schätzung; OECD-Staaten